Evidence for Resistance Training as a Treatment Therapy in Obesity - Barbara Strasser; Wolfgang Schobersberger (Journal of Obesity)
Over the last decade, investigators have paid increasing attention to the effects of resistance training (RT) on several metabolic syndrome variables. Evidence suggests that skeletal muscle is responsible for up to 40% of individuals' total body weight and may be influential in modifying metabolic risk factors via muscle mass development. Due to the metabolic consequences of reduced muscle mass, it is understood that normal aging and/or decreased physical activity may lead to a higher prevalence of metabolic disorders. The purpose of this review is to (1) evaluate the potential clinical effectiveness and biological mechanisms of RT in the treatment of obesity and (2) provide up-to-date evidence relating to the impact of RT in reducing major cardiovascular disease risk factors (including dyslipidaemia and type 2 diabetes). A further aim of this paper is to provide clinicians with recommendations for facilitating the use of RT as therapy in obesity and obesity-related metabolic disorders.